2016
DOI: 10.7150/jca.15605
|View full text |Cite
|
Sign up to set email alerts
|

Low Proteolytic Clipping of Histone H3 in Cervical Cancer

Abstract: Chromatin in cervical cancer (CC) undergoes chemical and structural changes that alter the expression pattern of genes. Recently, a potential mechanism, which regulates gene expression at transcriptional levels is the proteolytic clipping of histone H3. However, until now this process in CC has not been reported. Using HeLa cells as a model of CC and human samples from patients with CC, we identify that the H3 cleavage was lower in CC compared with control tissue. Additionally, the histone H3 clipping was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Acetylation, especially histone acetylation, plays a role in regulating gene expression . Alteration of histone 3 and 4 acetylation level has been observed in a variety of cancers, including cervical cancer . Histone deacetylase 1 (HDAC1) and HDAC2 are up‐regulated in cervical dysplasia and invasive cervical carcinoma .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acetylation, especially histone acetylation, plays a role in regulating gene expression . Alteration of histone 3 and 4 acetylation level has been observed in a variety of cancers, including cervical cancer . Histone deacetylase 1 (HDAC1) and HDAC2 are up‐regulated in cervical dysplasia and invasive cervical carcinoma .…”
Section: Introductionmentioning
confidence: 99%
“…9 Alteration of histone 3 and 4 acetylation level has been observed in a variety of cancers, including cervical cancer. 10,11 Histone deacetylase 1 (HDAC1) and HDAC2 are up-regulated in cervical dysplasia and invasive cervical carcinoma. 12 In cervical cancer HeLa cells, down-regulation of HDAC2 expression inhibited cell proliferation and induced cell cycle arrest.…”
mentioning
confidence: 99%
“…During the different stages of cervical cancer development, there is an accumulation of epigenetic alterations that leads to changes in gene expression [8]. Altered mechanisms of epigenetic regulation in cervical cancer include DNA methylation and post-translational modifications of histone proteins [8].…”
Section: Introductionmentioning
confidence: 99%
“…Altered mechanisms of epigenetic regulation in cervical cancer include DNA methylation and post-translational modifications of histone proteins [8]. It has been reported that histone modifying enzymes such as histone deacetylase (HDAC)-1 and HDAC2 are over-expressed in cervical dysplasia and invasive carcinoma [9].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, this method has also been used to study histone proteolysis [84]. As previously discussed, histone proteolysis has been reported to influence gene expression during cell differentiation, and has also been observed in cancer cell lines [46, 85]. Thus, understanding histone proteolysis can elucidate the pathologies of some diseases such as cervical cancer where histone proteolysis has also been reported [84].…”
Section: Analyzing In Vivo Proteolysis With Middle-down and Top-domentioning
confidence: 99%